ESTUDIOS PRELIMINARES DE LA MARCHITEZ Y PUDRICION DEL TALLO DEL CLAVEL DIANTHUS CARYOPHYLLUS - ROMERO C, SEBASTIAN; ESPINOZA M, ALFONSO (Centro de Economía Agrícola, Colegio de Posgraduados, 1973)
si
AGRO
Keywords: ESTUDIOS PRELIMINARES, MARCHITEZ, PUDRICION, TALLO DEL CLAVEL, DIANTHUS CARYOPHYLLUS; CIENCIAS AGRARIAS; HORTICULTURA; FLORICULTURA